PENGARUH INFLASI DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN DI INDONESIA - Rudy Susanto; Indah Pangesti (UNIVERSITAS INDRAPRASTA PGRI, 2020)
In the economic theory, inflation has an influence on the level of poverty, but the results of the analysis of this study indicate that inflation has no effect on the level of poverty based on research data for 2000-2019 obtained from the Central Statistics Agency. This study aims to determine and analyze the effect of inflation and economic growth on poverty levels in Indonesia. The research method used is descriptive quantitative using secondary data and data analysis methods are linear regression analysis, correlation analysis, determination analysis, and hypothesis testing. The results showed that inflation has no effect on the level of poverty due to the value of tcount < ttable, but economic growth has a significant effect on the poverty level because the value of tcount > ttable. Inflation and Economic Growth simultaneously have a significant effect on the Poverty Level as indicated by the value of Fcount > Ftable